Short term respiratory effects of acute exposure to chlorine due to a swimming pool accident. Issue 6 (1st June 2001) - Agabiti, N; Ancona, C; Forastiere, F; Di Napoli, A; Lo Presti, E; Corbo, G M; D'Orsi, F; Perucci, C A
Abstract : OBJECTIVE: Acute exposure to chlorine causes lung damage, and recovery may proceed slowly for several weeks. The short term respiratory effects of acute chlorine inhalation during a swimming pool accident were examined. METHODS: A total of 282 subjects (134 children, aged <14 years) inhaled hydrogen chloride and sodium hypochlorite during an accident caused by a malfunction of the water chlorinating system in a community pool in Rome in 1998. Most people received bronchodilators and cortisone at the emergency room; five children were admitted to hospital. A total of 260 subjects (92.2%) were interviewed about duration of exposure (<3, 3–5, >5 minutes), intensity of exposure (not at all or a little, a moderate amount, a lot), and respiratory symptoms. Lung function was measured in 184 people (82 children) after 15–30 days. The effects of exposure to chlorine were analysed through multiple linear regression, separately in adults and in children. RESULTS: Acute respiratory symptoms occurred among 66.7% of adults and 71.6% of children. The incidences were highest among those who had chronic respiratory disease and had a longer duration of exposure. In about 30% of the subjects, respiratory symptoms persisted for 15–30 days after the accident. Lung function levels were lower in those who reported a high intensity of exposure than in those who reported low exposure, both in children and in adults (mean (95% confidence interval (95% CI)) differences in forced expiratory volume in 1 second (FEV1, ) were −109 (−310 to 93) ml, and −275 (−510 to −40) ml, respectively). CONCLUSION: Persistent symptoms and lung function impairment were found up to 1 month after the incident. Although community pool accidents happen rarely, the medical community needs to be alerted to the possible clinical and physiological sequelae, especially among susceptible people.